Qingluo Tongbi Formula Alleviates Hepatotoxicity Induced by Tripterygium wilfordii Hook. F. by Regulating Excessive Mitophagy Through the PERK-ATF4 Pathway - Zhang, Linluo; Zhou, Jie; Feng, Zhe; Jiang, Baoping; Li, Changqing; Zhou, Lingling; Zhou, Xueping (Frontiers in Pharmacology, 2022)
Qingluo Tongbi Formula (QTF) is an empirical formula of Chinese medicine master Zhongying Zhou for the treatment of rheumatoid arthritis. Although including Tripterygium wilfordii Hook. f. (TW), it has not shown liver toxicity in clinical application for many years. Our previous studies have shown that QTF can significantly reduce TW-caused hepatotoxicity, but the mechanism is still unclear. This study aimed to explore the important roles of mitophagy and endoplasmic reticulum stress (ERS) and the relationship between them in QTF in alleviating TW-induced hepatotoxicity. In vivo, C57BL/6J female mice were used to build a model of TW-induced liver toxicity; Then mice were randomly divided into control, TW, TW+RG, TW+PN, TW+SA, TW+BM, and QTF groups. After intragastric administration for 7 days, the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) in serum were detected; H&E staining, Oil Red O staining, transmission electron microscopy, Western blotting, and RT-qPCR were used to detect the pathological changes in liver tissue, the levels of ERS and mitophagy related proteins and genes, including GRP78, PERK, DRP1, LC3, etc. In vitro, triptolide (TP), catalpol (CAT), and panax notoginseng saponins (PNS), the main active ingredients of QTF, were selected. The mitophagy inhibitor, ERS inhibitor, and PERK inhibitor were used to further study the relationship between TW-induced ERS and mitophagy in HepaRG cells. The results showed that, QTF reduced excessive mitophagy and ERS in TW-induced hepatotoxicity in C57BL/6J mice, and the attenuating effects of RG and PN in QTF were most obvious, and they also significantly restrained the TW-induced ERS and mitophagy by the PERK-ATF4 pathway. Furthermore, PNS was superior to CAT in inhibiting the expression levels of GRP78, PERK, and ATF4, while CAT was superior to PNS in reversing the expression levels of DRP1, P62, and LC3. The combination of CAT and PNS had the best attenuating effect and the most significant regulation on ERS and mitophagy. In conclusion, QTF can alleviate TW-induced hepatotoxicity by differentially downregulating the PERK-ATF4 pathway and excessive mitophagy by different components.